Effectiveness of pharmacotherapy for depression after traumatic brain injury in adults: an umbrella review protocol. Issue 7 (29th July 2021) - Hicks, Amelia J.; Clay, Fiona J.; James, Amelia C.; Hopwood, Malcolm; Ponsford, Jennie L.
ABSTRACT: Objective: The objective of this review is to synthesize systematic reviews of the effectiveness of pharmacotherapy vs any other comparator for the management of post-traumatic brain injury depression in adults. Introduction: Depression following a traumatic brain injury can have a considerable impact on the life of the individual, their family members, and the health care system. There have been several recent systematic reviews and meta-analyses on pharmacologic treatment for depression caused by post-traumatic brain injury. These reviews differ in conduct, quality, and reporting, and have discordant results and conclusions. Therefore, an umbrella review can provide prescribers with a summary of the evidence. Inclusion criteria: This review will consider systematic reviews of studies of adults 16 years or older who have sustained a traumatic brain injury of any severity at any time in the past, who are receiving pharmacotherapy for depression of any severity in any health care setting. Studies that include the following outcomes will be considered: change in symptoms of depression and occurrence of harms. Methods: MEDLINE, Embase, CINAHL, PsycINFO, Cochrane Database of Systematic Reviews, Epistemonikos, and PROSPERO will be searched, as well as Google Scholar, ResearchGate, TRIP Medical Database, and hand searching journals. There will be no restriction on publication date. Only systematic reviews published in English will be considered. Screening of articles, assessment of methodological quality, and data extraction will be performed independently by two reviewers. A Grading of Recommendations, Assessment, Development and Evaluation Summary of Findings will be presented. Data will be summarized in narrative form with supporting tables. Systematic review registration number: PROSPERO CRD42020184915